A Study on Customer Perception Towards Internet Banking: Identifying Major Contributing Factors - Singhal, Divya; Padhmanabhan, V. (Journal of Nepalese Business Studies, 2009)
Internet banking is becoming is increasingly becoming popular because of convenience and flexibility. The present paper explores the major factors responsible for internet banking based on respondents’ perception on various internet applications. It also provides a framework of the factors which are taken to assess the internet banking perception. The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 101-111